2014
DOI: 10.1515/pac-2014-5019
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for hybrid ab initio/molecular mechanical simulations of solutions: from complex chemistry to proton-transfer reactions and interfaces

Abstract: As a consequence of the ongoing development of enhanced computational resources, theoretical chemistry has become an increasingly valuable field for the investigation of a variety of chemical systems. Simulations employing a hybrid quantum mechanical/molecular mechanical (QM/MM) molecular dynamics (MD) technique have been shown to be a particularly promising approach, whenever ultrafast (i.e., picosecond) dynamical properties are to be studied, which are in many cases difficult to access via experimental techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 126 publications
2
20
0
Order By: Relevance
“…All simulations were carried out using the Quantum Mechanical Charge Field in C (QMCFC) program, 153,154,158,159,161,226,227 which implements both MM and QM/MM calculations, including application of TI. This program relies on an interface to the TURBOMOLE package 228,229 for the QM calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…All simulations were carried out using the Quantum Mechanical Charge Field in C (QMCFC) program, 153,154,158,159,161,226,227 which implements both MM and QM/MM calculations, including application of TI. This program relies on an interface to the TURBOMOLE package 228,229 for the QM calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Further details about the implementation can be found elsewhere. 153,154,158,159,161,226,227 The selected choices for the QM level of theory, basis sets, and population analysis scheme result from a balance between three constraints: (i) achieving a sufficient level of accuracy in the QM description; (ii) keeping the computational costs acceptable; (iii) balancing the QM and MM methodological choices so that they are mutually compatible. The importance of the third aspect in QMCF calculations cannot be overstated.…”
Section: S(x)mentioning
confidence: 99%
“…Today, four decades after these influential developments, QM/MM methods are regarded as one of the most influential approaches for the description of challenging chemical phenomena. Initially conceived in the framework of biomolecular simulations (Friesner and Guallar, 2005 ; Hu and Yang, 2009 ; van der Kamp and Mulholland, 2013 ; de Visser et al, 2014 ; Cui, 2016 ; Lu et al, 2016 ; Quesne et al, 2016 ), the range of QM/MM methods has been substantially extended to include other areas accessing inter alia solid-state chemistry and material science (Gonis and Garland, 1977 ; Krüger and Rösch, 1994 ; Stefanovich and Truong, 1996 ; Jacob et al, 2001 ; Herschend et al, 2004 ; Keal et al, 2011 ; Bjornsson and Bühl, 2012 ; Golze et al, 2013 , 2015 ; Hofer and Tirler, 2015 ) and solution chemistry (Staib and Borgis, 1995 ; Tuñón et al, 1995 , 1996 ; Gao, 1996 ; Hofer et al, 2010 , 2011 , 2012 ; Weiss and Hofer, 2012 ; Hofer, 2014 ) as well. These QM/MM studies have given insight into how Nature works, and, for instance, explain regio- and stereochemical selectivities during substrate activation (Faponle et al, 2016 , 2017 ; Timmins et al, 2017 ).…”
mentioning
confidence: 99%
“…(a) QM/MM setup in the QM charge field MD approach 21,23,161,162 for an ionic solute in a liquid system and (b) sketch of a 2D periodic QM/MM setup for the treatment of solid−liquid interfaces. 44,45 The Journal of Physical Chemistry C Here, N and Z represent the number of QM nuclei and their associated charges and M represents the number of MM PCs (the indices N and M are identical to eq 1). The respective distance vectors are given as r, and ∇ is the del operator, with the respective square corresponding to the Laplacian.…”
Section: Methodsmentioning
confidence: 99%
“…A typical research area benefiting from a QM/MM treatment is surface chemistry. It has been demonstrated that the application of a two-dimensional (2D) periodic QM treatment to the atoms near the interfacial region can be effectively combined with MM potentials to describe a sufficient number of atoms representing the bulk of the solid system , (see Figure ). In contrast to simplistic QM/MM approaches, which often rely on the application of position restraints that violate Newton’s third law of motion (i.e., the conservation of the linear momentum), no restraints are required in such a 2D QM/MM approach, that is, all atoms move freely according to the respective forces .…”
Section: Introductionmentioning
confidence: 99%